(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Within the ongoing initiatives to reinforce the identity of the Kayutangan heritage district in Malang, comprehension of architectural symbolism remains relatively constrained and is frequently limited to visual and formal dimensions. The Sacred Heart of Jesus Church (Kayutangan Church), as the sole manifestation of Neo-Gothic architecture within the area, encapsulates a complex symbolic system that has yet to be thoroughly and systematically investigated. This research seeks to classify the types of signs and to interpret the symbolic meanings embedded within Neo-Gothic architectural elements, while also formulating conservation implications grounded in meaning-based approaches. A Peircean semiotic framework was employed through the examination of 13 observational units, conducted in two sequential stages: the identification of Neo-Gothic architectural components and the subsequent analysis of sign–meaning relationships. Data collection was undertaken through a comprehensive literature review and field-based triangulation methods, including direct observation, in-depth interviews, and systematic documentation. The analytical process was structured around sign typologies, icon, index, and symbol, as well as architectural interpretations encompassing verticality, permeability, and religious symbolism. The findings indicate that nine architectural elements strongly articulate a Neo-Gothic identity, with symbolic signs emerging as the predominant category, primarily representing religious values rooted in ecclesiastical literature and Christian ideological frameworks. This study offers a significant contribution by elucidating the semiotic configuration of Neo-Gothic architectural elements and by proposing a conservation hierarchy informed by sign typologies and layers of meaning. It underscores the importance of safeguarding both symbolic form and interpretive meaning as fundamental components of architectural authenticity.